Minimally invasive steam-assisted drug delivery with ICG fluorescence guidance for primary malignant bone tumors and evaluation of clinical applicability - Seon Min Lee; Kicheol Yoon; Sangyun Lee; Hyun Guy Kang; Kwang Gi Kim (PLoS ONE, 2025)
Background Malignant bone tumors are rare cancers with a poor prognosis, often causing severe pain and pathological fractures that substantially reduce patients’ quality of life. Conventional cementoplasty can inhibit tumor cell proliferation but is limited by insufficient drug diffusion. To address this, we developed a minimally invasive drug delivery system utilizing high-temperature, high-pressure steam with integrated sensing and real-time temperature monitoring. Methods A drug delivery system consisting of a water tank, pump, and steam generator was designed and fabricated. The system was equipped with a monitoring unit capable of real-time temperature measurement and control. Results Large-animal experiments were conducted to evaluate the feasibility and distribution of steam injection in the femur. The procedure increased bone site temperatures to 48.8°C, as confirmed by fluorescence imaging. Discussion High-temperature steam successfully reached the target tissue; however, additional research is required to minimize collateral damage to normal bone. Future studies should focus on enhancing practicality by refining steam pressure and temperature control, optimizing nozzle design, and miniaturizing the device. Conclusion The proposed steam-based drug delivery system achieved broader tissue distribution than conventional methods, demonstrating potential as a novel treatment strategy for metastatic bone tumors. Further preclinical studies are warranted to support its clinical translation.